An examination of the products/services of Microfinance Institutions (MFIS) in Ghana-the case of GIFS - Opoku-Adade, Maureen (2016)
A Thesis submitted to the Department of Accounting and Finance, Kwame Nkrumah University of Science and Technology in partial fulfilment of the requirements for the degree of Master of Business Administration (Finance Option)